O impacto do fundo constitucional de financiamento do Nordeste sobre o crescimento dos estados - Santos Júnior, Paulo Roberto Mota dos (2021)
The present work aims to measure the impacts of the Constitutional Fund for Financing of the Northeast on the per capita product of the States in the Brazilian Northeast in the years following the financing. Panel data models are used with data for the period between 2003 and 2018. The results found indicate positive and significant effects of FNE disbursements on the state GDP per capita for all the specifications used. These effects show relative stability over the years. The results indicate the importance of the FNE for local economic growth and the need for continuity in the credit policy.